Optimalisasi Penguasaan Materi Garis dan Sudut Melalui Pendekatan Pembelajaran Berbasis Masalah di SMP - Suryana, Muhammad Fakhrudin (Muhammadiyah University Press, 2015)
This research surrounded by still have not optimal of domination of matter Demokrasi among student and implementation of study approach bases on problem at class student VIII E State Junior High School Three Teras Region Boyolali even semester of school year 2014/2015. This research aim to description about optimalisation of domination of matter line and angle through study approach bases on study internal issue of mathematics at class student VIII E State Junior High School Three Teras Region Boyolali. Subject and research data source is 24 students. Data collecting method applies observation, questionare, documentation, and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of class 100%. Research procedure applies cycle. Result of research and solution it is by know that data obtained from finite initial condition of cycle II, obtained progress of achievement of student learning in study of mathematics with matter line and angle through approach of problem based learning, at initial condition average of 72,1 and cycle I average of 76,4 and cycle II average of 84,4. From this data, seems to explain that happened increase of average of value from initial condition to cycle I 4,3 numbers (6%), from cycle I to cycle II happened increase equal to 8 number (10,5%), from precycle to cycle II happened increase 12,3 numbers (17,1%). Highest value of initial condition phase 82 and cycle I 86 and cycle II 92. Seems to explain that from initial condition phase to cycle I happened increase equal to 4 number (4,9%), from cycle I to cycle II happened increase equal to 6 number (7%), and from initial condition to cycle II happened increase 10 numbers (12,2%). Low value of initial condition phase is obtained by 66 and cycle I 70 and cycle II76. thereby, can be affirmed that from initial condition phase to cycle I happened increaseequal to 4 number (6%), from cycle I to cycle II happened increase equal to 6 number (8,6%), and from initial condition to cycle II happened increase 10 numbers (15,2%). Complete percentage learnt starts from initial condition is obtained equal to 27,3% and cycle I is obtained equal to 54,5% and cycle II equal to 100%. Seems to explain that from initial condition phase to cycle I happened increase equal to 27,2%, from cycle I to cycle II happened increase equal to 45,5%, and from initial condition to cycle II happened increase equal to 72,7%. Thereby, achievement of student learning in study of mathematics with matter line and angle through approach of problem based learning from finite initial condition of cycle II happened increase significant.